Modified release of furosemide from Eudragits® and poly(ethylene oxide)-based matrices and dry-coated tablets - Vlachou Marilena; Geraniou Efthymia; Siamidi Angeliki (Acta Pharmaceutica)
Modified release of furosemide from tablet formulations is preferred by patients, because of physiological problems, acute diuresis being the most serious, compared to the forms designed for immediate release. With this in view, we aimed at achieving furosemide’s longer gastric retention and waste minimization by preparing matrix and compression coated tablets incorporating different grades of Eudragit® and poly(ethylene oxide) (PEO), polyvinylpyrrolidone (PVP) and lactose monohydrate. Dissolution profiles of the new formulations were compared with that of the main stream drug Lasix®, 40 mg tablets. The results indicate that the use of Eudragit® in conjunction with either PVP or lactose monohydrate led to a slower release rate in the intestinal fluids compared to Lasix®. Moreover, furosemide release in the intestinal pH from matrix tablets and compression coated tablets was not noticeably different. Formulations incorporating PEO led to sustained release, in intestinal fluids, which depended on the molecular weight of PEO.